Higher education and its institutions in the Kingdom of Saudi Arabia 1957-1975 - Othman, Khalal Hammood (Al-Adab Journal, 2021)
This study showed that the Saudi Arabia witnessed a deteriorated social situations, which reflected even on the education in it, and its officials realized the importance of the education and the necessity of supporting it to escort the existing development in the foreign environment, which explained their sustain- in accordance with the then available capabilities- to that section.It is noticeable that the university education did not find any care and interest only in a late period of time, the fact which was related to the predominant social conditions, as society's eyesight to the education and its importance.Nevertheless, the 1950s decade had witnessed the universities founding movement, followed by horizontal expansion process that expanded in accordance with the kingdom's need.At the same time, it didn't seem that the kingdom delayed to seek the help of foreign experience, especially when it was lacking to academic-scientific cadres. From this point, the kingdom devoted to make use of that experience, hence it sent scientific scholarships abroad, at the same time, it put an educational policy on which it drew its plans concerning build up the lower constructions, and being noticed that the development that accompanied universities foundation, by students getting higher scientific marks inside the kingdom and outside, is considered as a goal which the Saudian governments have always tried to achieve